EPR spectroscopy of multicomponent, multispin molecular system obtained by the photolysis of 2, 4, 6‐triazido‐3‐cyano‐5‐fluoropyridine in solid argon. (3rd June 2019) - Chapyshev, Sergei V.; Korchagin, Denis V.; Grote, Dirk; Sander, Wolfram
Abstract: Complex multicomponent, multispin molecular system, consisting of a septet trinitrene, two quintet dinitrenes, and three triplet mononitrenes, was obtained by the photolysis of 2, 4, 6‐triazido‐3‐cyano‐5‐fluoropyridine in solid argon. To identify these paramagnetic products, electron paramagnetic resonance spectroscopy in combination with line‐shape spectral simulations and density functional theory calculations was used. The products of the photolysis was found to be triplet 2, 4‐diazido‐3‐cyano‐5‐fluoropyridyl‐6‐nitrene ( D T = 1.000 cm −1, E T = 0), triplet 2, 4‐diazido‐3‐cyano‐5‐fluoropyridyl‐2‐nitrene ( D T = 1.043 cm −1, E T = 0), triplet 2, 6‐diazido‐3‐cyano‐5‐fluoropyridyl‐4‐nitrene ( D T = 1.128 cm −1, E T = 0 cm −1 ), quintet 4‐azido‐3‐cyano‐5‐fluoropyridyl‐2, 6‐dinitrene ( D Q = 0.211 cm −1, E Q = 0.0532 cm −1 ), quintet 2‐azido‐3‐cyano‐5‐fluoropyridyl‐4, 6‐dinitrene ( D Q = 0.208 cm −1, E Q = 0.0386 cm −1 ), and septet 3‐cyano‐5‐fluoropyridyl‐2, 4, 6‐trinitrene ( D S = −0.1017 cm −1, E S = −0.0042 cm −1 ) in a 38:4:7:22:14:4 ratio, respectively. Abstract : The yields and molecular structures of septet trinitrene, two quintet dinitrenes and three triplet mononitrenes, obtained by photolysis of 2, 4, 6‐triazido‐3‐cyano‐5‐fluoropyridine in solid argon, were established, using matrix EPR spectroscopy in combination with spectral simulations and density functional theory calculations.